GRAIN BOUNDARY SLIDING IN SUPERPLASTICITY FORMING of TITANIUM ALLOYS (Ti6Al4V) - Armila Armila (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2020)
The major property of super plastic material is the high strain rate sensitivity (m ≥ 0.3), which provides high resistance to necking growth, the extension can be obtained is very high (e> 500%) without breaking. decent to obtain high m, the material requirements must have been a fine grain size, where the grain size (d≤ 10µm) is equal-axial or round and stable at high deformation temperatures. Grain boundary sliding is a process in grains slide passing each other, or in the zone directly adjacent to, their common boundary In-situ observation of grain boundary sliding using electron microscopy. The material must be fine-grained, because at super plastic at high temperatures the main deformation mechanism is